Andare ausiliare del passivo deontico - Cinque, Guglielmo (Verbum – Analecta Neolatina, 2025)
The Italian auxiliary andare ‘go’ is ambiguous between a purely passive usage and a modal (deontic) passive one. The two uses differ with respect to a number of properties, which are examined here. The pure passive usage is more constrained than the modal (deontic) usage as it is possible with only few verbs (of ‘loss’ and ‘disappearance’), and unlike the ordinary passive construction does not admit an agentive phrase. In this article particular attention is dedicated to the second, modal (‘deontic’) passive, usage.